2019
DOI: 10.1542/peds.2019-0904
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring the Life-Span Benefits of Newborn Screening

Abstract: Newborn screening is a highly successful public health program that has led to major improvements in outcomes for a variety of conditions otherwise associated with long-term disability and even death. 1 In the United States, newborn screening is provided to every newborn, regardless of circumstance, leading to the identification of .13 000 newborns with a significant condition each year. 1 Most of these individuals require specialized care over their life span. However, public health involvement in newborn scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…With a robust long-term follow-up component, GDSP values the necessity of monitoring all potential cases, including those with a VUS [ 46 ]. The growing knowledge from long-term follow-up will further improve our understanding of the clinical significance of these cases, especially when case management algorithms are still undeveloped for asymptomatic patients [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…With a robust long-term follow-up component, GDSP values the necessity of monitoring all potential cases, including those with a VUS [ 46 ]. The growing knowledge from long-term follow-up will further improve our understanding of the clinical significance of these cases, especially when case management algorithms are still undeveloped for asymptomatic patients [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…A population-based United Kingdom study from 1999 to 2003 identified that 23% of patients diagnosed with an IEM were diagnosed in adulthood, with a separate cohort revealing 40% of IEM diagnoses were made in adulthood [ 5 , 7 ]. NBS has also resulted in the diagnosis of patients that may not present until late adolescence or adulthood as has been seen in late-onset glutaric acidemia type 2, carnitine palmitoyl transferase deficiency type 2, medium-chain acyl-CoA dehydrogenase deficiency, primary carnitine deficiency, X-linked adrenoleukodystrophy, and late onset Pompe Disease [ 8 ]. Clinical practice guidelines and management algorithms are still being developed for these individuals detected “pre-symptomatically”, and the degree to which these individuals follow up and receive care later in life for these adult-onset conditions is largely unknown, and beyond the scope of this paper [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…NBS has also resulted in the diagnosis of patients that may not present until late adolescence or adulthood as has been seen in late-onset glutaric acidemia type 2, carnitine palmitoyl transferase deficiency type 2, medium-chain acyl-CoA dehydrogenase deficiency, primary carnitine deficiency, X-linked adrenoleukodystrophy, and late onset Pompe Disease [ 8 ]. Clinical practice guidelines and management algorithms are still being developed for these individuals detected “pre-symptomatically”, and the degree to which these individuals follow up and receive care later in life for these adult-onset conditions is largely unknown, and beyond the scope of this paper [ 8 ]. The diagnosis of IEMs in adults outside of newborn screening is often difficult due to attenuated phenotypes, variable expressivity, missed diagnoses in childhood, considerable overlapping phenotypes with other disorders, and under recognition by providers [ 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The primary goal of NBS is to detect and treat infants with diverse diseases in a timely manner in order to prevent health impairment and infant mortality [3,15]; however, since most of the diseases detected by NBS are genetic, it is not uncommon to find other affected or deceased members in the family, especially older siblings, who carry the same condition [16]. Our results support this, since we found 26 affected older siblings, and 10 (38.5%) of them had severe clinical consequences of the disease, including intellectual disability (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Newborn screening (NBS) has proven to be an effective public health program to prevent or diminish the morbidity and mortality associated with a range of disorders [1][2][3]. Almost all the diseases detected by NBS are genetic, and most of them have an autosomal recessive mode of inheritance, which means that both parents are asymptomatic carriers and that in each pregnancy, there is a 25% risk of having an affected child [4].…”
Section: Introductionmentioning
confidence: 99%